Paradigma Moderasi Beragama dalam Pancasila Sila Pertama - Zahrotun Nikmah; M. Nasyat Fayyadh U; Naufan Sadida Rashif; Muhammad Zaenaal M (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The relationship between religious moderation and the first precept of Pancasila is that every religious person believes that the God they worship is One or one, but the general public of Indonesia does not know very well the religion other than the one he adheres to. The problems that arise due to the ignorance of the community make the author interested and motivated to provide an understanding of this through this article. The method used in the study is a qualitative method with a case study approach. Each religion has its own meaning regarding the One Godhead, every religion in Indonesia has similarities regarding the meaning of God Almighty. This concept of divinity is relevant to the First Precept of Pancasila. The first precept of Pancasila as one of the foundations for religious moderation has clearly represented various religions in Indonesia, not just dominating one religion. This shows how Indonesia's ideology.